2003
DOI: 10.1093/rheumatology/keg316
|View full text |Cite
|
Sign up to set email alerts
|

Paucity of Sjogren-like syndrome in a cohort of HIV-1-positive patients in the HAART era. Part II

Abstract: It is concluded that SLS, the prevalence of which in the pre-HAART era was 7.8%, has disappeared, possibly as a result of the protective action of HAART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 13 publications
4
23
0
1
Order By: Relevance
“…The findings in the present study on the effect of HAART on cryoglobulinemia agree with previous studies demonstrating a beneficial effect of HAART in other autoimmune conditions that are associated with HIV infection [Caso et al, 1999;Reveille, 2000;Salliot et al, 2002;Zandman-Goddard and Shoenfeld, 2002;Panayiotakopoulos et al, 2003], but are in contrast with other studies showing an exacerbation of autoimmune manifestations after HAART due to immune reconstitution [Diri et al, 2000;Jubault et al, 2000]. A possible explanation for this discrepancy may be that different pathogenetic mechanisms underlie various autoimmune phenomena.…”
Section: Discussionsupporting
confidence: 93%
“…The findings in the present study on the effect of HAART on cryoglobulinemia agree with previous studies demonstrating a beneficial effect of HAART in other autoimmune conditions that are associated with HIV infection [Caso et al, 1999;Reveille, 2000;Salliot et al, 2002;Zandman-Goddard and Shoenfeld, 2002;Panayiotakopoulos et al, 2003], but are in contrast with other studies showing an exacerbation of autoimmune manifestations after HAART due to immune reconstitution [Diri et al, 2000;Jubault et al, 2000]. A possible explanation for this discrepancy may be that different pathogenetic mechanisms underlie various autoimmune phenomena.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, antiviral drugs may be an effective treatment for virus-induced xerostomia. In point of fact, the prevalence of DILS has significantly decreased among cohorts of HIV patients since the introduction of highly active antiretroviral treatment (HAART) (1,36).…”
Section: Discussionmentioning
confidence: 99%
“…Although HAART is important in improving outcomes for PLWHA, its effect on the development of autoimmune diseases is unclear 6. A previous epidemiological study showed that the prevalence of autoimmune disease (eg, Sjögren syndrome) significantly decreased after the initiation of HAART among PLWHA 7. However, a case report suggested that HAART could cause immune restoration inflammatory syndrome and might trigger development of autoimmune diseases 8.…”
Section: Introductionmentioning
confidence: 99%